2007
DOI: 10.1002/polb.21274
|View full text |Cite
|
Sign up to set email alerts
|

Cationic poly(methacryl oxyethyl trimethylammonium) and its poly(ethylene glycol)‐grafted analogue as capillary coating materials in electrophoresis

Abstract: Cationic polyelectrolytes were synthesized and used as semipermanent coating materials for capillaries in electrophoresis. The polyelectrolytes used were a homopolymer of poly(methacryl oxyethyl trimethylammonium chloride) (PMOTAC) and its poly(ethylene glycol) (PEG)-grafted analogue. Two PMOTAC polyelectrolytes, with molar masses of 85,000 and 300,000 g/mol, and PEG-grafted PMOTAC with a molar mass of 280,000 g/mol were synthesized and then characterized by size exclusion chromatography (SEC) and nuclear magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…The reproducibility of the EOF mobility was still as low as 0.5% (RSD) for 25 repetitions after 1 month. The stability of the capillaries was excellent and greatly improved compared to that observed earlier in studies of PMOTAC‐coated capillaries due to the covalent grafting of the capillary surface.…”
Section: Resultsmentioning
confidence: 61%
“…The reproducibility of the EOF mobility was still as low as 0.5% (RSD) for 25 repetitions after 1 month. The stability of the capillaries was excellent and greatly improved compared to that observed earlier in studies of PMOTAC‐coated capillaries due to the covalent grafting of the capillary surface.…”
Section: Resultsmentioning
confidence: 61%
“…The EOF directly after the coating process was ‐4.57·10 −8 m 2 ·V −1 ·s −1 (RSD 0.68%; n = 5) for PMOTAI and ‐4.14·10 −8 m 2 ·V −1 ·s −1 (RSD 1.62%; n = 5) for PIL‐1 using phosphate buffer at pH 7.4 (ionic strength of 10 mM). Lower stability for freshly coated capillary was found with similar structure polyelectrolyte poly(methacryl oxyethyl trimethylammonium chloride) with M W of 85 000 and 300 000 g/mol . Both PECs exhibited bleeding from the capillary, which can be seen from the continuously decreasing mobility of EOF (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, we observed further decrease of EOF at pH 11 (especially for PIL‐1) and a substantial increase in the RSD values (5.44% for PMOTAI and 9.29% for PIL‐1; n = 5). Higher instability in the basic pH region has also been observed earlier when using similar PECs in CE . Moreover, Nehmé et al .…”
Section: Resultsmentioning
confidence: 99%
“…‘Static’ adsorbed coatings are particularly attractive, including numerous homopolymers such as poly(ethylene oxide) (PEO) 19, hydroxyethylcellulose (HEC) 20, poly(vinyl alcohol) (PVA) 21, poly( N , N ‐dimethylacrylamide) (PDMA) 22, 23, poly( N ‐hydroxyethylacrylamide) (PHEA) 1, polyethyleneimine 24, polybrene 25, chitosan 26, and so on. Among them, PEO, poly(ethylene glycol) (PEG, the low‐molecular mass form of PEO), and their derivatives (such as PEG methyl ether methacrylate (PEGMA)), are well known to be the most desirable and effective molecules for reducing the surface adsorption of proteins 27–29. However, they still face some problems, e.g.…”
Section: Introductionmentioning
confidence: 99%